Assessing Farmers' Willingness to Accept "Greening": Insights from a Discrete Choice Experiment in Germany. (16th October 2013) - Schulz, Norbert; Breustedt, Gunnar; Latacz‐Lohmann, Uwe
Abstract This paper explores farmers' prospective responses to the "greening" of the Common Agricultural Policy. The analysis is based on discrete choice experiments with 128 German farmers. Participants were asked to choose between a "greening" option with a given set of management prescriptions and an "opt‐out" alternative with a stipulated cut of the single direct payment. A binary logit model is used to identify the variables affecting the likelihood of "greening" being chosen. In addition, latent class estimations are carried out to group respondents into latent classes of "compliers" and "non‐compliers". We find that farmers' choices are driven by "greening" policy attributes, personal and farm characteristics, and interactions between these two groups of variables. Farmers perceive "greening" as a costly constraint, but not all farmers are equally affected and not all "greening" provisions are regarded as equally demanding. Specialised arable farms on highly productive land and intensive dairy farms are most likely to opt out of "greening" and voluntarily forgo part of their single payment entitlements. The paper concludes with a set of recommendations for improving the design of a second‐best policy.